"Self-Governance" Good Moral and Ethical Role Model of Educational Administrators - Hongsaipin, Nattapat; Visitthapanyo, Phramaha Pisit (Journal of Graduate MCU KhonKaen Campus, 2025)
Self-conduct is a fundamental moral and ethical principle that educational administrators should uphold as a guiding framework for appropriate behavior in alignment with their roles, responsibilities, and institutional context. This article conceptualizes self-conduct as the foundation of being a role model in educational leadership, explained through three integrated theoretical frameworks: (1) Ethical Leadership, which emphasizes integrity, transparency, fairness, and accountability; (2) Good Governance, which highlights participation, responsibility, transparency, rule of law, and effectiveness in organizational management; and (3) Buddhist principles, particularly the Threefold Training (Sĩla, Samãdhi, Paññă), the Four Sublime States (Brahmavihăra), and the qualities of a virtuous person (Sappurisa-dhamma), which focus on holistic self-development in moral discipline, mental cultivation, and wisdom. The integration of these frameworks demonstrates that self-conduct is not merely an individual characteristic but a strategic leadership mechanism that fosters trust, credibility, and acceptance among teachers, staff, students, parents, and the community. Such moral leadership enables administrators to effectively manage people and tasks while cultivating an organizational culture grounded in ethics and governance. Ultimately, self-conduct grounded in ethical leadership, good governance, and Buddhist principles serves as a critical foundation for sustainable educational quality and exemplary leadership in a rapidly changing era.